Efficacy of Music Therapy on Immediate Postpartum Episiotomy Pain: A randomized controlled trial - Ravita Chaichanalap; Wipada Laosooksathit; Kittipong Kongsomboon; Tharangrut Hanprasertpong (Thai Journal of Obstetrics and Gynaecology, 2018)
Objectives: To evaluate the effectiveness of music therapy in alleviating immediate postpartum episiotomy wound pain. Materials and Methods: A randomized controlled trial was conducted to evaluate the efficacy of music therapy in alleviating immediate pain from an episiotomy wound. Uncomplicated singleton vaginal delivery women with the second degree or less episiotomy wound at Delivery and Postpartum Inpatient Unit, Department of Obstetrics and Gynecology, Faculty of Medicine, Srinakharinwirot University, Thailand were enrolled into the study. Visual analog scale (VAS) scoring was used for comparing pain levels.Results: One hundred postpartum women were enrolled in our study. Baseline characteristics such as age, degree of episiotomy wound tear were similar between both groups. The median pain VAS score was statistically significantly lower in the music group than in the control group at the end of the 2nd hour after finish of episiotomy wound repairing process [24.0 millimeters (8.3-41.5) and 36.5 millimeters (20.0-53.3), p < 0.001]. The median pain VAS score was statistically significantly lower in the music group than in the control group at the end of 6th hour after finish of episiotomy wound repairing process [12.0 millimeters (3.0-21.0) and 22.0 millimeters (15.0-38.0), p < 0.001] Conclusion: Music therapy is effective for reducing the perceived immediate postpartum pain of an episiotomy wound.